Respuesta :

Answer and Step-by-step explanation:

The answer you should be getting is [tex]x=4[/tex]

Step 1: Simplify both sides of the equation :

[tex](\frac{-1}{2})(x)+(\frac{-1}{2})(2)+\frac{3}{2}x=3[/tex]  [tex](Distribute)[/tex]

[tex]\frac{-1}{2}x+-1+\frac{3}{2}x=3[/tex]

[tex](\frac{-1}{2}x+\frac{3}{2}x)+(-1)=3[/tex]  [tex](Combine the like terms)[/tex]

[tex]x+-1=3[/tex]

[tex]x-1=3[/tex]

Step 2: Add 1 to both the sides :

[tex]x-1+1=3+1[/tex]

[tex]x=4[/tex]

You got your answer as x = 4

ACCESS MORE